Design of the "Up2U" domestic abuse perpetrator programme. Issue 3 (9th July 2018) - Pearson, Dominic A.S.; Ford, Amy
Abstract : Purpose: The purpose of this paper is to outline the development, structure, and implementation of a new programme for domestic abuse (DA) perpetrators. Design/methodology/approach: A needs-led DA perpetrator programme is proposed, named as "Up2U: Creating Healthy Relationships" (Up2U). The background to Up2U, its aims, configuration, and delivery methods are presented in this paper. To illustrate Up2U, the targets for change and referral population in the development site are discussed. Furthermore, the paper reflects on some of the implementation decisions and the steps taken towards evaluating the impact of Up2U in the development site. Findings: Research supports provision of treatment targeting perpetrators' criminogenic needs, delivered with responsivity to their learning styles, at an intensity that matches their risk. Change on treatment targets can be evaluated in the context of differences in recidivism outcomes to help assess whether impact can be attributed to the programme. It can also serve as a more proximal index of success/failure for individual clients. Such implementation and evaluation decisions are a benefit of the present researcher-practitioner partnership. Originality/value: Up2U is innovative by being risk-and needs-led rather than taking a gendered approach to DA treatment, and this new evidence-based approach may reduce partner abuse. This is the first paper to outline Up2U's structure, content, implementation, and measurement.